Henrique Novaes: técnica, território e cidade em uma trajetória profissional: Brasil, primeira metade do século XX - Julianelli, Anna Rachel Baracho Eduardo (2012)
The career of civil engineer Henrique de Novaes, a remarkable figure in the academic, technical and political fields, demonstrates its extensive and relevant work across Brazil in the first half of the twentieth century. It covered from the design of water supply and sewage works, road and rail transport networks, works against drought in the Northeast, hydroelectric and harbor facilities to the urbanization planning and architectural projects, which displays a systematic and multiple production. City and territory conformed to his fields of verification, practical and above all, transformation. The search for understanding of the inclusion of a social actor in this process thus contributes to the specific analysis of the doings of Henrique de Novaes, who graduated at Polytechnic School of Rio de Janeiro in 1906. From a polymorphic activity in different scales, one tries to figure how, through academic education or professional practice, urban history in Brazil can be told or built. The introduction of technological innovations matched the purposes of planning and urban sprawl, as well as met the specifications of regulation and institutionalization of public infrastructure services at the time. The overall plans proposed by the engineer thought of the city as a whole, interconnected to the structural networks. At the same time, the knowledge of a larger physical scale the territory bounces back in the urban in a relationship of reciprocity and completeness. The objective research, therefore, tries to understand the roles played by Henrique de Novaes s works and academic education in the accomplishment of systematic modernization of Brazilian urban space and territory, recovering a little known historical figure by current historiography. It is proposed, as methodological axis, that the study of this professional career configures itself as an essential element for understanding the idea of progress embodied in the technical studies and proposals for improvements and sanitation nationwide in the first half of the twentieth century . The primary sources for the construction of this analysis were technical articles in journals of the period ( Clube de Engenharia , Viação e Revista Brasileira de Engenharia ), and technical reports, government messages, newspaper articles published at the time, autobiographical reports and the engineer s verbal communications with relatives. The work is structured in three chapters: "Biographical traces, academic education and 'technical and political' activities" illustrates the initiation into the technical, public and political environment; Chapter 2, "Technique and territory" outlines his network understanding through sanitation and transport services; Chapter 3 "Technique and City" describes the influence of polytechnics knowledge on the propositions of modernization of cities; Finally, "Final Thoughts: An Evaluation," presents an overview of the affiliations and practice of an engineer in the different scales, and its contribution to the modernization of Brazilian urban and territorial space